Reconsidering the limited role of right heart catheterization on severe pulmonary hypertension-due to progressive interstitial lung disease in young male patient : a case report - Megawati Abubakar; Anggoro Budi Hartopo; Ika Trisnawati; Eko Budiono; Dyah Wulan Anggrahini; Lucia Kris Dinarti (Universitas Gadjah Mada, 2023)
Pulmonary hypertension (PH)-associated with interstitial lung disease (ILD) develops as a consequence of progressive underlying lung disease or disproportionately to the underlying disease. The PH investigation by right heart catheterization (RHC) for defining PH severity is recommended in patients with ILD who show more severe symptoms than expected from lung disease, appearance of right heart failure, and clinical deterioration not matched by the declining lung function. In patient with progressive ILD, RHC is only considered if it affects the future treatment such as lung transplantation or enrollment in clinical trial/registry. The decision to undertake the RHC in progressive ILD was still fraught with doubts. Here we reported a young adult male patient with ILD whom developed progressive signs and symptoms. By RHC, he had severe precapillary PH with hemodynamic parameters indicated the presence of pulmonary vascular disease. A PH-specific treatment, sildenafil citrate, was administered, and patient responded well and was clinically stable during the addition of sildenafil citrate. This case highlights the clinical implication of performing RHC in progressive ILD, which can change the treatment decision by PH-specific drugs. Therefore, the RHC decision making in patient with progressive ILD need reconsideration.